2019
DOI: 10.1039/c9tc03176f
|View full text |Cite
|
Sign up to set email alerts
|

Ti2VGe Heuslerene: theoretical prediction of a novel 2D material

Abstract: The possibility of a new graphene-like slice of the Heusler compounds, named Heuslerene, is predicted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(10 citation statements)
references
References 61 publications
0
10
0
Order By: Relevance
“…Nonetheless, novel HAs are being studied theoretically due to fast computational facilities to predict their structural, electronic states, spin orientation, magnetic moment, bonding, mechanical, thermodynamic and thermoelectric properties. The recent first principles studies on some Co‐based, 44‐49 Fe‐based, 36,38,50‐53 Zr‐based 54‐56 and Ti‐based with new dimensions 57 HAs showed keen interest. As far as the research of Mn‐based full HAs is concerned, Mn 2 VAl was found the first full HA investigated in theoretical 58‐60 and experimental 61 research.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, novel HAs are being studied theoretically due to fast computational facilities to predict their structural, electronic states, spin orientation, magnetic moment, bonding, mechanical, thermodynamic and thermoelectric properties. The recent first principles studies on some Co‐based, 44‐49 Fe‐based, 36,38,50‐53 Zr‐based 54‐56 and Ti‐based with new dimensions 57 HAs showed keen interest. As far as the research of Mn‐based full HAs is concerned, Mn 2 VAl was found the first full HA investigated in theoretical 58‐60 and experimental 61 research.…”
Section: Introductionmentioning
confidence: 99%
“…The theoretical background of the elastic constants along with the calculation of parameters such as bulk modulus, Shear modulus, Debye temperature, and … for bulk materials with cubic symmetry have been reported in our previous reports [62,63]. Moreover, as represented in our recent work [47], the theoretical background of the elastic constants for 2D materials as well as their appropriate amounts for the Heuslerene Ti 2 VGe were investigated by using IRelast2D package [64] which worked as an interface with Wien2k code [65]. It should be noted that the experimental investigation of the elastic constants of 2D materials is a challenge for scientists at present [66] and so, such a package (IRelast2D) might be the best alternative which opens a new theoretical way for investigating the mechanical properties of 2D systems.…”
Section: Stability Of Co2cral and Its 2d Sheetsmentioning
confidence: 79%
“…The physical properties of the ground state of bulk and heuslerene of the Co 2 CrAl compound were studied based on density functional theory (DFT) by full potential linearized augmented plane waves (FP-LAPW) [46,47]. Then, the effects of exchange-correlation potential on the calculations of electronic properties in the Wien2K [65] code were investigated by GGA [48], GGA+U [49][50], and GGA+U+mBJ [51,52] approximations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Multifunctional materials represent a dynamic research area for both industrialists as well as for the scientific community to meet the overwhelming demands of spintronics, thermoelectric (TE), and other innovative technologies. [1][2][3][4][5][6] A search for new materials with smart electronic properties has trigged the research interests. The discovery of new novel materials with promising capabilities to meet the challenges for new technological applications.…”
Section: Introductionmentioning
confidence: 99%